Parallel Operation of DC Converters in Isolated Pv-Wind DC Microgrid using Droop - Sharma, Pabitra; Bhusal, Priya; Adhikari, Pujan; Baral, Rajiv; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2023)
With the increasing consumer loads operated by DC voltage, DC micro-grids are becoming popular in terms of reliability and efficiency. In DC micro-grids, a conventional droop control method has been used to share the load proportionally to their capacity; however it led to the reduction of reference bus voltage. This paper presents an adaptive droop controller designed to mitigate the trade-off between current sharing and voltage regulation of the DC micro-grid. To simulate and evaluate the suggested control approach, isolated dc-dc converters are used. The proposed scheme is simulated using MATLAB Simulink and the simulation results show that the control logic for adaptive droop control works satisfactorily.